Processing of pictorial food stimuli in patients with eating disorders: a systematic review - Giel, Katrin; Teufel, Martin; Friederich, Hans-Christoph; Hautzinger, Martin; Enck, Paul; Zipfel, Stephan (The international journal of eating disorders, 2011)
Objective: The processing of food cues in eating-disordered patients has recently been increasingly investigated. Outlined is current evidence from pictorial food stimuli studies. Method: PubMed and PsychINFO were searched for quantitative pictorial food stimuli studies investigating healthy controls and expert-diagnosed eating-disordered patients. Results: Patients with eating disorders (ED) demonstrated cue reactivity to food stimuli. Results from functional imaging suggest sensory disengagement and higher emotional involvement while self-reported data and facial EMG revealed that food pictures were perceived as less pleasurable. Different experimental paradigms have demonstrated an attentional bias for food cues in ED. Currently, psychophysiological data is widely inconclusive. Discussion: Evidence suggests cue reactivity to food pictures in eating-disordered patients. However, the overall picture is inconclusive because methodological problems and the integration of findings from different experimental approaches pose a challenge to the research field. © 2010 by Wiley Periodicals, Inc.